1994
DOI: 10.1093/jac/33.suppl_a.121
|View full text |Cite
|
Sign up to set email alerts
|

Nitrofurantoin modified release versus trimetfaoprim or co-trimoxazole in the treatment of uncomplicated urinary tract infection in general practice

Abstract: A total of 538 patients from 45 different general practice centres across the UK was admitted to an open study and randomized to one of the following treatment groups: nitrofurantoin modified release (MR) 100 mg bd, trimethoprim 200 mg bd or co-trimoxazole 960 mg bd. Each patient received seven days of medication. Clinical cure, defined as relief from symptoms at visit 2, occurred in 87.2% of the patients treated with nitrofurantoin MR, 84.5% of the co-trimoxazole group and 86.5% of the trimethoprim group. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…For simplicity, the Figure does not include the probability of vaginal yeast infection, which was calculated for each outcome on the basis of published probabilities. 7,[22][23][24][25] Other potential antibiotic effects or complications (eg, StevensJohnson syndrome) were considered rare and not included in our model, given that a previous investigation of uncomplicated UTIs found that expensive but uncommon events had almost no effect on overall treatment costs. 26 Finally, a model was constructed that compared all 3 treatments: nitrofurantoin, TMP-SMX, and fluoroquinolones.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For simplicity, the Figure does not include the probability of vaginal yeast infection, which was calculated for each outcome on the basis of published probabilities. 7,[22][23][24][25] Other potential antibiotic effects or complications (eg, StevensJohnson syndrome) were considered rare and not included in our model, given that a previous investigation of uncomplicated UTIs found that expensive but uncommon events had almost no effect on overall treatment costs. 26 Finally, a model was constructed that compared all 3 treatments: nitrofurantoin, TMP-SMX, and fluoroquinolones.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, nitrofurantoin has retained a high prevalence of sensitivity to most uropathogens and has a favorable side-effect profile. 7 A recently published randomized trial demonstrated that nitrofurantoin for 5 days is as effective as TMP-SMX for 3 days in treating acute UTI in women. 8 Moreover, nitrofurantoin, like TMP-SMX, is less expensive than fluoroquinolones in many communities.…”
Section: Mayo Clinmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1967 a macrocrsitalline form with improved gastrointetinal tolerance became available [20,25,33]. Nowadays, there are two basic presentations of nitrofurantoin: the macrocrystalline form and a mixture of the microcrystalline and macrocrystalline forms (25 mg macrocristals plus 75 mg monohydrate form) [25,33], blended in a patented dual delivery system, which is known in USA as nitrofurantoin monohydrate/macrocristals [34]. For therapy of UTIs nitrofurantoin in the macrocrystalline formulation is given orally at 50 to 100 mg four times daily [20,25].…”
Section: Management Of Acute Uncomplicated Cystitismentioning
confidence: 99%
“…For therapy of UTIs nitrofurantoin in the macrocrystalline formulation is given orally at 50 to 100 mg four times daily [20,25]. The dose of the mixture of microcrystalline and macrocrystalline formulation is 100 mg twice a day [25,33,34]. This latter presentation is not commercialized in Spain.…”
Section: Management Of Acute Uncomplicated Cystitismentioning
confidence: 99%